THE GUIDELINE FOR PROMOTING A HAPPY WORKPLACE ORGANIZATION BASED ON THE PRINCIPLE APARIHANIYADHAMMA OF BAN NONGHIN SCHOOL, NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 3 - Kukkaew , Kowit; Yotharak, Maliwan; Samakhkhi, Pricha (Journal of Educational Review Faculty of Education in MCU, 2026)
The study aimed to study the current conditions in development of the creative leadership of school administrators in Cha-Uat District, to investigate the development of the creative leadership based on The Viddhi-Dhamma of school administrators in Cha-Uat District, and to propose guidelines for the development of the creative leadership based on The Viddhi-Dhamma for school administrators Cha-Uat District. The study was conducted employing a qualitative research method. Key informants from the interviews were 15 participants, 5 experts and 7 specialists in group discussion. The research tools employed were in-depth interviews, expert interviews, and group discussion. Qualitative data were analyzed using content analysis to assess feasibility, appropriateness, and usefulness. The findings were as follows: 1) The current conditions in development of the creative leadership of school administrators in Cha-Uat District found that in terms of imagination, school administrators inspire and encourage teamwork, providing teachers with opportunities to express their opinions and develop new innovations. However, obstacles include slow operations and a lack of clarity, leading to uncertainty and conflicts. Regarding flexibility, administrators listen to the opinions of personnel and are open to change, resulting in creative development and a positive learning environment. However, challenges include delays in implementation, resistance, and a lack of support from school personnel. In terms of vision, administrators set clear and creative goals, ensuring a definite direction for operations while allowing school personnel to participate in achieving success. This fosters motivation and commitment among staff toward school development. Nevertheless, obstacles such as a lack of understanding among personnel, insufficient internal support, and limited resources hinder the full realization of the intended vision. With regard to trust, administrators acknowledge differing viewpoints and promote fair organizational progress, leading to an improved working atmosphere. However, a lack of clarity sometimes causes confusion and uncertainty among staff. Concerning creativity, administrators emphasize skill and experience enhancement among personnel while encouraging teamwork. This fosters openness to learning and continuous professional development. However, conflicts may arise due to resistance from personnel who oppose creative approaches. 2) Guidelines for promoting a happy organization based on the principles of Aparihaniyadhamma at Ban Nong Hin School, under the Nakhon Si Thammarat Primary Educational Service Area Office 3, consist of six elements: good health (Happy Body), kindness and willingness to help others (Happy Heart), moral integrity (Happy Soul), positive social relationships (Happy Society), eagerness for learning (Happy Brain), and happiness at work (Happy Work-life). These elements are applied through the seven principles of Aparihaniyadhamma, which include: (1) holding regular meetings, (2) attending meetings in unity, (3) accepting the resolutions of the meetings, (4) obeying superiors, (5) respecting and protecting the rights of women or the vulnerable, (6) showing respect for sacred places, and (7) taking care of and showing hospitality to visitors. 3) As for the proposal of a guideline in the development of strategic leadership based on The Viddhi-Dhamma school administrators in Cha-Uat District was found to be feasible, appropriate, and beneficial.